2010
DOI: 10.1016/j.juro.2010.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Management of Surgical and Radiation Induced Rectourethral Fistulas With an Interposition Muscle Flap and Selective Buccal Mucosal Onlay Graft

Abstract: Successful rectourethral fistula closure can be achieved for nonradiated (100%) and radiation/ablation (84%) rectourethral fistulas using a standard anterior perineal approach with an interposition muscle flap and selective use of buccal mucosal graft, providing a standard for rectourethral fistula repair. Even the most complex radiation/ablation rectourethral fistula can be repaired avoiding permanent urinary and fecal diversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 17 publications
1
55
1
1
Order By: Relevance
“…In our series a single investigator performed this in patients who underwent energy ablation. 12 Concomitant bladder neck contracture or urethral stricture was more common in the energy ablative cohort (26.0% vs 14.2% of cases, p ¼ 0.03).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In our series a single investigator performed this in patients who underwent energy ablation. 12 Concomitant bladder neck contracture or urethral stricture was more common in the energy ablative cohort (26.0% vs 14.2% of cases, p ¼ 0.03).…”
Section: Resultsmentioning
confidence: 89%
“…6,10,12 We discuss the management and combined outcomes of RUF after prostate cancer treatment at 4 reconstructive urology centers where there is experience with managing these cases.…”
mentioning
confidence: 99%
“…Although it is impossible to conclude much due to the small case numbers in this study, we also should pay attention to urinary incontinence after transperineal repair for URF because there is a risk of sphincter impairment. Urethral catheters were maintained for a median duration of 2 months post operation; this duration was slightly longer than that in other studies [5,10] . Based on the existing situation, these periods are determined differently in each of the institutions.…”
Section: Discussionmentioning
confidence: 84%
“…Several possible factors affecting results of URF repair have been reported [5,[8][9][10] . Some papers suggested that complicated fistulas with a large diameter, previous failed repair surgery, or previous irradiation are negative predictive factors for the successful closure of fistulas.…”
Section: Discussionmentioning
confidence: 99%
“…Komplizierend hierbei sind häufig gleichzeitig bestehende urethrale Strikturen. Vanni et al[35] berichten in einem Kollektiv von 39 Patienten über eine Erfolgsquote von 84% bei Anwendung eines perinealen Zugangswegs mit Fistelverschluss und Interposition eines M.-gracilis-Lappens bei einem Follow-up von median 20 Monaten. Bemerkenswert hierbei ist ein Anteil von 28% an Patienten mit simultan bestehender Urethrastriktur, die mit einem Mundschleimhautpatch in Onlay-Technik versorgt wurde.…”
unclassified